Determinación de la influencia de las condiciones climáticas en la captura de carbono en un sistema theobroma sp “cacao” con sombra en alto el sol - Valera Garcia, Raissa Karel (2013)
This work was carried out in order to determine the iníluence of climatic conditions in the carboncapture in the system with Theobroma sp cocoa in High shade the Sun - Pachiza- 2012. In the Community of High Sun, one comes implemented mechanisms of carbon sequestration to reduce greenhouse gas emissions and to increase their catch in soils and biomass, for this has been reforestation withcedro, caoba, estoraque, paliperro, capirona and other species in areas within the agricultura! holdings. The action ofthe population not only stimulate significant changes in the soilmanagement; also, by means of an increase in the content of organic matter will have a significant impact in their direct properties and have a positive impact on the environmental qualities and on biodiversity.The consequences will include increased soil fertility and productivity of the land for food production and food security. This inexpensive too] will also make the fanning practices more sustainable and help to prevent or mitigate the degradation of the earth resources.Weather conditions '(temperature, relative humidity, precipitation) during the study period (20 11-20 12), are of relevan ce with respect to the historical pattern (2007 - 201 1 ), being the average monthly rainfall in the months of October to December which recorded the largest mcrease m relation to the historical pattern. Regarding the growth of the cultivation of cocoa, the volumetric increase in m3 is carried out consistently with the months of September to December, the Iargest increase by volume, however in the months of March there is an alteration to growth this is due to the cultural work of harvest. The climatic conditions are closely related to the increase of biomass and carbon capture, with the months of June to August the that recorded the biggest increase in this fund raising (51.17 kg biomass and carbon 22.58 kg), being the rainfall in our region that influences directly in the carbon sequestration, due to the nutrients in the soil are admitted with the water to the root system and they are moved by the vascular bundles, already that the groundwater is used with the co2 to form the carbohydrate in the plant species through the photosynthetic activity. According to the data recorded in the laboratory samples we appreciate that the pH of the soil is 6.5 this tells us that this is a ground of reaction very close to the neutral, and that there is no congestion problems in aluminum, that is to saythere are no problems of acidity, in addition the chemical elements r~:quired by the :.